Study Some Properties of a Circulant Matrix - Akram Salim Mohammed (Tikrit Journal of Pure Science)
The aim of this paper is to study the properties of idempotent, nilpotent and stability to a circulant matrix  which generated by the first row, finally we showed the relation between this properties with eigenvalues of this matrix.